Promoting Creative Learning in Social Studies by Exploring Floating Cage Fish Cultivation Activities as Learning Resources - Mutiani Mutiani; Ersis Warmansyah Abbas; Hendry Alfiani Ari Sandi; Syaharuddin Syaharuddin; Jumriani Jumriani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This article describes how creative learning is by integrating contextual social studies learning resources. This matter is based on social studies learning must be able to accommodate students' critical and creative thinking. As a research instrument, the researcher conducted structured interviews and non-participatory observations. Data analysis using the interactive model of Miles and Huberman reduces interview and documentation data; presentation of data through descriptive narratives; documentation; and concluding. The study results describe the activities of floating net cage fish farming in Banua Anyar Village in RT 03, RT 04, and RT 05. In terms of floating net cage fish farming activities, there are two main activities: production and consumption. The floating net cage fish farming activity in Banua Anyar Village indicates the suitability of the Human, Place, and Environment learning material for class VII semester I. This material is presented in social studies subjects which cover the discussion of the natural conditions of Indonesia (the physical condition of the region), which includes the discussion of actions, motives, and economic principles. The relationship between floating net cage fish farming activities as social studies learning resources provides room for confirmation of contextual examples from students' closest lives. Therefore, the formulation of creative learning can be designed based on floating net cage fish farming activities as social studies learning resource.